Characterization of bacteriocin producing bacterial strains from fermented vegetables - Siti Hazirah Aw Al Ud-din (2014)
Bacteriocins are protein that produced by bacteria and are antagonistic to other bacteria. Bacteriocins have potential application in food and feed industry because of their antibacterial characteristics. In this study, bacterial strains from fermented vegetables were isolated and characterized for bacteriocin production. A total of ten bacterial strains were isolated and identified from fermented vegetables. Out of these, two were determined the ability to inhibit the growth the indicator strains Escherichia coli, Aeromonas spp. and Flavobacterium spp. The isolates were identified based on their morphologically characteristics. Bacteriocin was produced from cell-free supernatant and antimicrobial activity of bacteriocin was studied by well diffusion method. Bacteriocin stability was studied in different temperature, pH and salinity. Bacterial strains isolated from fermented vegetable were found to be capable of producing bacteriocin and inhibiting the wide range of pathogenic bacteria. Production of bacteriocin was positively influenced by the pH and the highest production was obtained at pH 4. However, complete inactivation of antimicrobial activity from temperature and salinity influenced was also observed. Nevertheless, bacteriocin producing bacteria from fermented vegetables in this research could act as a potential barrier to inhibit the growth of bacteria that cause diseases in food and served as an alternative source of antibiotic for the use in disease treatment in aquaculture.